A foamed polyethylene insulation material for category 6A communication cables

CN122978561APending Publication Date: 2026-10-27GUANGZHOU KINGSENS POLYMER SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611221299.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,传统弹性体由于分子链结构匹配性问题,降低界面张力的效果有限;而普通PE-g-MAH由于其基体树脂的分子量分布较宽、支链规整性不足,导致接枝官能团在界面处的分布不够连续和均匀,难以在高浓度PP添加量下兼顾材料的刚性与韧性

Benefits of technology

1.兼顾高硬度与高韧性,机械力学性能优异

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a foamed polyethylene insulating material for a 6A type communication cable and belongs to the field of high polymer materials. The material comprises high-density polyethylene, low-density polyethylene LDPE, polypropylene, a compatilizer, a nucleating agent masterbatch, an antioxidant and a lubricant. The application introduces polypropylene combined with a maleic anhydride grafted metallocene polyethylene compatilizer, significantly reduces the interfacial tension of the system by using the regular and continuous interface transition layer of the compatilizer, improves the hardness of the foamed material to enhance the deformation resistance of the wire, avoids the excessive rigidity of the material, and makes the material have excellent tensile strength and elongation at break. Meanwhile, the introduction of the nucleating agent masterbatch can regulate the crystallization morphology, improve the melt strength, effectively inhibit the bubble collapse and bulging defects in the processing process, and obviously improve the wire ovality. The combination of the antioxidant and the lubricant endows the material with excellent thermal stability and long-term hot air aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to polymer materials, and particularly relates to a foamed polyethylene insulation material for Category 6A communication cables. Background Technology

[0002] In 5G communication and data center cabling technologies, Category 6A network cables, as core cabling products supporting 10Gbps high-speed transmission, have stringent specifications for signal attenuation performance in the low-frequency band (less than 10MHz). Currently, the insulation layer of Category 6A network cables typically uses physically foamed polyethylene (PE) material, utilizing its low dielectric constant to meet the requirements of high-frequency transmission. However, traditional physically foamed PE materials have relatively high molecular chain flexibility and low melt strength, resulting in insufficient hardness of the cured foamed insulation layer. During core wire twisting and subsequent cable processing, the insulation layer is prone to structural deformation under external mechanical stress, manifesting as cell collapse and excessive ellipticity of the wire. This reduces the relative positional stability between the internal conductor and the insulation layer, resulting in a low low-frequency attenuation margin (typically only 0.1dB to 0.15dB).

[0003] To improve the physical hardness of the insulation layer, polypropylene (PP) is often introduced for blending modification, utilizing the rigidity of the PP molecular chain to improve its resistance to deformation. However, in practical applications, the commonly used homopolymer PP has extremely high molecular chain regularity and crystallinity, resulting in very poor interfacial compatibility between it and the non-polar PE matrix. During melt blending, the solubility parameters of the two materials deviate, leading to high interfacial tension and significant phase separation. This interfacial defect significantly increases the brittleness of the blended material and deteriorates its mechanical properties. The tensile strength of its sheets and wires typically drops below 12 MPa, and the elongation at break drops below 300%, failing to meet the mechanical strength requirements of relevant standards (such as UL444) for communication cables.

[0004] To address interfacial compatibility issues, conventional polyethylene-grafted maleic anhydride (PE-g-MAH) or styrene-based elastomers are often introduced as compatibilizers in existing technologies. However, traditional elastomers have limited effectiveness in reducing interfacial tension due to molecular chain structure matching issues; while ordinary PE-g-MAH, due to the wide molecular weight distribution and insufficient branch regularity of its matrix resin, results in an insufficiently continuous and uniform distribution of grafted functional groups at the interface, making it difficult to balance the rigidity and toughness of the material even with high concentrations of PP.

[0005] Therefore, how to improve the melt strength and hardness of physically foamed polyethylene insulation while ensuring that the material has both excellent tensile strength and elongation at break is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The first objective of this invention is to provide a foamed polyethylene insulation material for Category 6A communication cables, comprising the following components in parts by weight: High-density polyethylene, 40-80 parts; Low-density polyethylene (LDPE), 5-15 parts; Polypropylene, 5-15 parts; Compatibilizer, 1-5 parts; Nucleating agent masterbatch, 0.1-1 part; Antioxidant, 0.1-0.5 parts; Lubricant, 0.1-1.5 parts.

[0007] Preferably, the melt index of the high-density polyethylene at 190°C and 2.16 kg is 0.5-1.5 g / 10 min; The polypropylene is a copolymer polypropylene with a melt index of 2-10 g / 10 min.

[0008] Preferably, the low-density polyethylene (LDPE) has a melt index of 4-8 g / 10 min at 190°C and 2.16 kg.

[0009] Preferably, the compatibilizer is maleic anhydride-grafted metallocene polyethylene.

[0010] Preferably, the nucleating agent masterbatch is prepared from azodicarbonamide and low-density polyethylene.

[0011] Preferably, the antioxidant is a hindered phenol; and the lubricant is calcium stearate.

[0012] A second objective of this invention is to provide a method for preparing the aforementioned foamed polyethylene insulation material for Category 6A communication cables, comprising the following steps: 1) Add high-density polyethylene, low-density polyethylene (LDPE), polypropylene, compatibilizer, nucleating agent masterbatch, antioxidant and lubricant to a mixing tank in proportion and mix to obtain a mixture. 2) The mixture is added to a twin-screw extruder for extrusion granulation to obtain modified masterbatch; 3) The modified masterbatch is added to a foaming extruder, melted, and then injected with nitrogen gas. The mixture is then foamed and molded through a die.

[0013] In step 1), the mixing tank is a high-speed mixing tank, and the mixing time is 5-10 minutes; In step 2), the extrusion temperature of the twin-screw extruder is controlled between 190-210℃, and the main machine speed is 300-500 rpm / min.

[0014] In step 3), the melting temperature inside the foaming extruder is 180-200℃, the injected nitrogen pressure is 12-18MPa, and the foaming degree is controlled at 55%-65%.

[0015] The method further includes the following steps: 4) After foaming, the insulation layer is cooled and shaped by water at 20-30℃, and then insulated wire cores with a diameter of 2.2-2.8mm are produced at a traction speed of 10-20m / min.

[0016] The present invention has the following beneficial effects: 1. It combines high hardness and high toughness, exhibiting excellent mechanical properties. This invention improves the rigidity and deformation resistance of the matrix material by introducing polypropylene, and matches it with maleic anhydride-grafted metallocene polyethylene as a dedicated compatibilizer. The unique narrow molecular weight distribution and uniform branched structure of metallocene polyethylene result in a more regular and continuous distribution of polar groups at the interface, significantly reducing the interfacial tension between polyethylene and polypropylene. While greatly improving the hardness of the insulation layer and reducing wire stranding deformation, it effectively suppresses the risk of brittle fracture that is easily caused by traditional modifications, giving the material both excellent tensile strength and elongation at break.

[0017] 2. Improve extrusion processing performance and reduce wire ellipticity. By incorporating specific nucleating agent masterbatches into the formulation, the crystal morphology and crystal structure of the polyolefin components can be controlled during processing, reducing dielectric loss. In continuous processing and melt foaming, this system effectively enhances melt strength, suppresses defects such as cell collapse and flattening, and significantly improves the ellipticity and roundness of the final wire. Detailed Implementation

[0018] To better understand the present invention, the present invention will be further described below with reference to specific serial numbers. The terminology used in the serial numbers is for describing specific embodiments and does not constitute a limitation on the scope of protection of the present invention.

[0019] In the specific implementation methods, unless otherwise specified, the experimental methods used are all conventional methods, and the materials and reagents used are all commercially available unless otherwise specified.

[0020] Unless otherwise specified, percentages, etc. in the specific implementation method are assumed to be mass percentages.

[0021] The specific specifications of the raw materials used in the various embodiments and comparative examples of this invention are as follows: High-density polyethylene: model 8380, with a melt index (MI) of 0.5-1.5 g / 10 min at 190℃ and 2.16 kg.

[0022] Low-density polyethylene (LDPE): Model C7100, with a melt index (MI) of 4-8 g / 10 min at 190℃ and 2.16 kg.

[0023] Polypropylene: Grades include 7533 (copolypropylene), 7633, W331, and CJS700, with a melt index (MI) of 2-10 g / 10 min.

[0024] Compatibilizers: Brands include HS3-012X (maleic anhydride-grafted metallocene polyethylene), HS3-012B (maleic anhydride-grafted metallocene polyethylene), and 573A (ordinary polyethylene grafted with maleic anhydride).

[0025] Nucleating agent masterbatch: Model 0012, made from azodicarbonamide and low-density polyethylene.

[0026] Antioxidant: Model number 1010, a hindered phenol.

[0027] Lubricant: Model BS-3818, calcium stearate.

[0028] Example 1 This embodiment provides a foamed polyethylene insulation material for Category 6A communication cables, the formulation of which, by weight percentage, comprises: High-density polyethylene 8380. 71.7%. Low-density polyethylene LDPEC7100, 12%, Polypropylene 7533, 10%, Nucleating agent masterbatch 0012, 1% Compatibilizer HS3-012X, 4% Antioxidant 1010, 0.3%, Lubricant BS-3818, 1%.

[0029] Its specific preparation method includes the following steps: 1) Add high-density polyethylene 8380, low-density polyethylene LDPEC7100, polypropylene 7533, compatibilizer HS3-012X, nucleating agent masterbatch 0012, antioxidant 1010 and lubricant BS-3818 into a high-speed mixing tank according to the proportion, and mix at room temperature for 8 minutes to obtain a uniformly mixed material. 2) The uniformly mixed material is added to a twin-screw extruder for extrusion granulation. The extrusion temperature of the twin-screw extruder is controlled at 200℃ and the main machine speed is 400rpm / min. Modified masterbatch is obtained by extrusion granulation. 3) The modified masterbatch is added to a foaming extruder, melted at 190°C, and then injected with nitrogen gas at a pressure of 15 MPa. The mixture is then foamed through a die, with the foaming degree controlled at 60%. 4) After foaming, the insulation layer is cooled and shaped at 25°C, and then traction is carried out at a speed of 15m / min to finally produce an insulated wire core with a diameter of 2.5mm.

[0030] Example 2 This embodiment provides a foamed polyethylene insulation material for Category 6A communication cables, the formulation of which, by weight percentage, comprises: High-density polyethylene 8380, 69.7%, Low-density polyethylene LDPEC7100, 12%, Polypropylene 7533, 12%, Nucleating agent masterbatch 0012, 1% Compatibilizer HS3-012B, 4% Antioxidant 1010, 0.3%, Lubricant BS-3818, 1%.

[0031] The specific preparation method is the same as in Example 1, except that the corresponding proportions of components and the brand of compatibilizer are changed in step 1).

[0032] Comparative Example 1 This comparative example describes a foamed polyethylene insulation material for Category 6A communication cables, the formulation of which, by weight percentage, comprises: High-density polyethylene 8380, 76.7%, Low-density polyethylene LDPEC7100, 12%, Polypropylene 7633, 10%, Nucleating agent masterbatch 0012, 1% Antioxidant 1010, 0.3%, Lubricant BS-3818, 1%.

[0033] The specific preparation method and steps are the same as in Example 1, and no compatibilizer is added to the formula.

[0034] Comparative Example 2 This comparative example describes a foamed polyethylene insulation material for Category 6A communication cables, the formulation of which, by weight percentage, comprises: High-density polyethylene 8380, 76.7%, Low-density polyethylene LDPEC7100, 12%, Polypropylene W331, 10%, Nucleating agent masterbatch 0012, 1% Antioxidant 1010, 0.3%, Lubricant BS-3818, 1%.

[0035] The specific preparation method and steps are the same as in Example 1, and no compatibilizer is added to the formula.

[0036] Comparative Example 3 This comparative example describes a foamed polyethylene insulation material for Category 6A communication cables, the formulation of which, by weight percentage, comprises: High-density polyethylene 8380, 71.7%, Low-density polyethylene LDPEC7100, 12%, Polypropylene CJS700, 10% Nucleating agent masterbatch 0012, 1% Compatibilizer 573A, 4%, Antioxidant 1010, 0.3%, Lubricant BS-3818, 1%.

[0037] The specific preparation method is the same as in Example 1, and ordinary polyethylene grafted with maleic anhydride is used as a compatibilizer in the formula.

[0038] Performance testing and evaluation The modified materials and wires obtained in Examples 1-2 and Comparative Examples 1-3 were subjected to performance tests, and the test standards and methods are as follows: 1) Sheet tensile strength and elongation at break test: conducted according to GB / T1040.3-2006, with the tensile speed controlled at 50 mm / min; 2) Wire tensile strength and elongation at break test: conducted according to UL2556-2021, with the tensile speed controlled at 250 mm / min; 3) Shore hardness test: Performed according to GB / T2411-2008, with a sample thickness of 4 mm and a test reading time of 15 s; 4) Insulation heat shrinkage test: Conducted according to GB / T2951.13-2008, with the test temperature set at 100℃ and the duration at 1h.

[0039] The specific performance test results are shown in Table 1: Table 1 Performance test results of Examples 1-2 and Comparative Examples 1-3 In Table 1, the insulation heat shrinkage is marked as " / " because no significant displacement was observed under the accuracy of the testing instrument, indicating that it is below the detection limit.

[0040] According to the experimental data in Table 1: 1) A comparison of the data from Example 1 and Example 2 shows that as the amount of polypropylene added to the system increases from 10% to 12%, the overall hardness and strength of the material remain at a high level, while the elongation is somewhat controlled. Under this test system, the material exhibits superior comprehensive mechanical properties when the amount of polypropylene added is 10%.

[0041] 2) Comparison of data from Comparative Example 1 and Comparative Example 2 shows that in the blend system without compatibilizer, the elongation at break of the material decreased significantly, indicating that the interfacial compatibility between the specific homopolymer polypropylene and the polyethylene matrix is ​​poor, which leads to increased crystalline brittleness of the material. In contrast, the copolymer polypropylene and the low-density polyethylene (LDPE) matrix show a relatively good compatibility trend, which is beneficial to improving the toughness of the matrix.

[0042] 3) Comparison of data from Comparative Example 2 and Comparative Example 3 shows that after introducing ordinary polyethylene grafted maleic anhydride (PE-g-MAH, grade 573A) as an interfacial compatibilizer into the formulation, the tensile strength of the blend system slightly increased and the elongation at break increased significantly. This indicates that the intervention of the polar compatibilizer effectively reduced the interfacial tension between non-polar matrices and improved the compatibility between the blend components.

[0043] 4) A comparison of the data from Example 1 with Comparative Examples 2 and 3 shows that, under the same matrix ratio, when maleic anhydride-grafted metallocene polyethylene (mPE-g-MAH) is used as a dedicated compatibilizer, the tensile strength and elongation at break of the sheet and wire materials of the present invention significantly increase. This confirms that a metallocene polyethylene matrix with a narrow molecular weight distribution and a uniform branched structure can impart higher rigidity and hardness to the grafted material, and its polar functional groups are more regularly and continuously distributed, thereby improving the material's hardness while avoiding the risk of rigid brittle fracture caused by the introduction of components.

[0044] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A foamed polyethylene insulation material for Category 6A communication cables, characterized in that, The components include the following parts by weight: High-density polyethylene, 40-80 parts; Low-density polyethylene (LDPE), 5-15 parts; Polypropylene, 5-15 parts; Compatibilizer, 1-5 parts; Nucleating agent masterbatch, 0.1-1 part; Antioxidant, 0.1-0.5 parts; Lubricant, 0.1-1.5 parts.

2. The foamed polyethylene insulation material according to claim 1, characterized in that: The high-density polyethylene has a melt index of 0.5-1.5 g / 10 min at 190℃ and 2.16 kg. The polypropylene is a copolymer polypropylene with a melt index of 2-10 g / 10 min.

3. The foamed polyethylene insulation material according to claim 1, characterized in that: The low-density polyethylene (LDPE) has a melt index of 4-8 g / 10 min at 190°C and 2.16 kg.

4. The foamed polyethylene insulation material according to claim 1, characterized in that: The compatibilizer is maleic anhydride-grafted metallocene polyethylene.

5. The foamed polyethylene insulation material according to claim 1, characterized in that: The nucleating agent masterbatch is prepared from azodicarbonamide and low-density polyethylene.

6. The foamed polyethylene insulation material according to claim 1, characterized in that: The antioxidant is a hindered phenol; the lubricant is calcium stearate.

7. A method for preparing the foamed polyethylene insulating material according to any one of claims 1-6, characterized in that, Includes the following steps: 1) Add high-density polyethylene, low-density polyethylene (LDPE), polypropylene, compatibilizer, nucleating agent masterbatch, antioxidant and lubricant to a mixing tank in proportion and mix to obtain a mixture. 2) The mixture is added to a twin-screw extruder for extrusion granulation to obtain modified masterbatch; 3) The modified masterbatch is added to a foaming extruder, melted, and then injected with nitrogen gas. The mixture is then foamed and molded through a die.

8. The preparation method according to claim 7, characterized in that: In step 1), the mixing tank is a high-speed mixing tank, and the mixing time is 5-10 minutes; In step 2), the extrusion temperature of the twin-screw extruder is controlled between 190-210℃, and the main machine speed is 300-500 rpm / min.

9. The preparation method according to claim 7, characterized in that: In step 3), the melting temperature inside the foaming extruder is 180-200℃, the injected nitrogen pressure is 12-18MPa, and the foaming degree is controlled at 55%-65%.

10. The preparation method according to claim 7, characterized in that, The method further includes the following steps: 4) After foaming, the insulation layer is cooled and shaped by water at 20-30℃, and then insulated wire cores with a diameter of 2.2-2.8mm are produced at a traction speed of 10-20m / min.